Alveogyl: Foreign Body Reaction. (2nd April 2021) - Joshi, Sandeep; Steel, Clare; Eyeson, Josiah
Abstract : Alveolar osteitis (AO) is a painful complication experienced by approximately 3–4% of patients who have undergone a dental extraction. A frequently used intra-alveolar dressing material, such as Alveogyl is commonly used to treat sockets where a diagnosis of AO is made. However, unexpected problems may be encountered by the dentist when using such materials and this article explores a case where a diagnosis of a foreign body reaction to Alveogyl was identified in a symptomatic patient with no overt clinical or radiographical signs. CPD/Clinical Relevance: Dental professionals should be aware of the possible complications with the use of Alveogyl in the treatment of alveolar osteitis, in particular foreign body reactions.